2019
DOI: 10.21608/bvmj.2019.15171.1053
|View full text |Cite
|
Sign up to set email alerts
|

Detection of shiga toxin strains of Escherichia coli non O157 in different soft cheese by polymerase chain reaction

Abstract: The objectives of the current study were detection and characterization of the isolated Escherichia coli non O157 using PCR assay. A total of 90 cheese samples high salt soft cheese, Kareish cheese and Tallaga cheese were examined for E. coli non O157 using modified vancomycin-trypticase soy broth and Sorbitol MacConkey agar plates. Serodiagnosis of E. coli non-O157 has been done using slide agglutination test. Toxigenic E. coli non-O157 isolates were detected using PCR assay. Results postulated that the detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…As illustrated in Table ( 1), E. coli could be isolated from Tallaga cheese samples with an incidence rate of 10%. A similar finding was obtained by Taha et al (2019), while a higher result was investigated by Raghda et al (2021).…”
Section: Disscusionsupporting
confidence: 84%
See 2 more Smart Citations
“…As illustrated in Table ( 1), E. coli could be isolated from Tallaga cheese samples with an incidence rate of 10%. A similar finding was obtained by Taha et al (2019), while a higher result was investigated by Raghda et al (2021).…”
Section: Disscusionsupporting
confidence: 84%
“…In another study, (Atef Yekta et al, 2010) discovered that using 0.5 to 10 mg/ml and 0.1 to 10 mg/ml of human or bovine lactoferrin, respectively, E. coli O157:H7 growth was considerably reduced in broth from three to six hours after incubation. Furthermore, Taha et al (2019) found that all concentrations of lactoferrin caused a significant decrease in P < 0.05 on the viability of E. coli O1 isolated from Kareish cheese after 72 h in broth at the concentration of 10 and 20 mg/ml lactoferrin.…”
Section: Disscusionmentioning
confidence: 91%
See 1 more Smart Citation